WIP and WICH/WIRE co-ordinately control invadopodium formation and maturation in human breast cancer cell invasion - Garcia,E; Ragazzini,C; Yu,X; Cuesta-Garcia,E; Bernardino,de la Serna J; Zech,T; Sarrio,D; Machesky,LM; Anton,IM (Scientific Reports, 2016)
Cancer cells form actin-rich degradative protrusions (invasive pseudopods and invadopodia), whichallows their efficient dispersal during metastasis. Using biochemical and advanced imaging approaches,we demonstrate that the N-WASP-interactors WIP and WICH/WIRE play non-redundant roles incancer cell invasion. WIP interacts with N-WASP and cortactin and is essential for invadopodiumassembly, whereas WICH/WIRE regulates N-WASP activation to control invadopodium maturationand degradative activity. Our data also show that Nck interaction with WIP and WICH/WIRE modulatesinvadopodium maturation; changes in WIP and WICH/WIRE levels induce differential distribution ofNck. We show that WIP can replace WICH/WIRE functions and that elevated WIP levels correlate withhigh invasiveness. These findings identify a role for WICH/WIRE in invasiveness and highlight WIP asa hub for signaling molecule recruitment during invadopodium generation and cancer progression, aswell as a potential diagnostic biomarker and an optimal target for therapeutic approaches.